Behavioural effect of soil transmitted helminths control programme among school going children in Meru County, Kenya - Ngechu, Judith N.; Onyango, Rosebella; Wafula, Charles; Kamau, Peter (International Journal Of Community Medicine And Public Health, 2023)
Background: Intestinal parasitic infections are major public health problems mostly among children contributed in part by adults in developing countries. Despite the effort of World Health Organization (WHO) to eradicate intestinal parasitic infections, the infection continues to be the most common of tropical diseases in developing countries. Methods: This study adopted a mixed methods design, specifically the convergent parallel mixed methods research design. Data was collected using questionnaires, key informants guide, observation and stool examination for intestinal parasitic infections which were administered to both the experimental groups and the control groups. Data analysis was carried out with the aid of statistical package of the social sciences (SPSS) version 26.0, using descriptive statistics to describe the characteristics of the studied population. Qualitative data was analyzed by thematic content analysis. Results: Washing hands after visiting the toilet (p<0.05), washing hands before eating (p<0.05) and washing hands after playing (p<0.05) were significantly associated with intestinal parasitic infections in both intervention and control groups. Further, at post intervention, in the intervention group, the overall prevalence of protozoan infections reduced from 28.0% to 14.7% before and after intervention respectively as well the overall prevalence of helminthic infections reduced from 40.3% to 13.7% before and after intervention respectively. Conclusions: Public health interventions influenced the reduction of the prevalence of intestinal parasites. The county government should play a role in interventions to improve sanitation and hygiene in communities. Public health offices should enforce skills training and enhancement at the household level, and multiple targeted interventions focused on intestinal parasite infections should be implemented.